Assessing the structural, morphological and magnetic properties of polymer-coated magnesium-doped cobalt ferrite (CoFe2O4) nanoparticles for biomedical application. (October 2019) - Mokhosi, SR; Mdlalose, W; Mngadi, S; Singh, M; Moyo, T
Abstract: In this study, we have functionalised cobalt ferrite (CoFe2 O4 ) nanoparticles (NPs) by doping with a natural bio-mineral magnesium (Mg) and coating with three polymers to enhance biocompatibility and feasibility for therapeutic applications. The glycol-thermal method was employed to synthesise CoFe2 O4 and Mg0.5 Co0.5 Fe2 O4 NPs. The latter NPs were functionalised with chitosan (CHI), poly-ethylene glycol (PEG) and poly-vinyl alcohol (PVA) to produce CHI-Mg0.5 Co0.5 Fe2 O4, PEG-Mg0.5 Co0.5 Fe2 O4 and PVA-Mg0.5 Co0.5 Fe2 O4 . The structure and morphology of NPs were characterized using transmission electron microscopy (TEM), high resolution TEM (HR-TEM), X-ray diffraction (XRD), Fourier transform infra-red (FTIR) spectroscopy and nanoparticle tracking analysis (NTA). Magnetic measurements were carried out using a vibrating sample magnetometer (VSM). XRD patterns confirmed inverse cubic spinel phase structure typical of ferrite NPs. NPs exhibited spherical shape with average size diameters of ranging between 8 nm and 11 nm. Coating increased these average size diameters up to 13 nm. Zeta potential measurements indicated low colloidal stability of the NPs which improved considerably with PEG and PVA coating. FTIR confirmed surface modifications seen in additional peaks characterised by amine and carbonyl groups for chitosan and PEG/PVA, respectively. CoFe2 O4 NPs exhibited high saturation magnetisations of 73.861 emu/g. This value decreased with magnesium-doping and polymer-coating due to shielding effect. In vitro cytotoxicity analysis demonstrated significant tolerability of coated Mg0.5 Co0.5 Fe2 O4 NPs at concentrations of 800 μg/ml in cervical cancer (HeLa) cell lines. Conclusively, these polymer-coated ferrites present feasible nanocarriers in magneto-targeted drug delivery.